2015
DOI: 10.1155/2015/505989
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Microtubular La0.6Sr0.4Ti0.2Fe0.8O3−δMembrane by Electrophoretic Deposition for Hydrogen Production

Abstract: Microtubular type La0.6Sr0.4Ti0.2Fe0.8O3−δ(LSTF) membranes were prepared by electrophoretic deposition (EPD). The oxygen permeation and hydrogen production behavior of the membranes were investigated under various conditions. LSTF green layer was successfully coated onto a carbon rod and, after heat treatment at 1400°C in air, a dense LSTF tubular membrane with a thickness of 250 mm can be obtained. The oxygen permeation and hydrogen production rate were enhanced by CH4in the permeate side, and the hydrogen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The research results of Wang et al [24] and Lee at al. [13] both revealed that, based on the water splitting reaction and oxygen permeation process in a membrane reactor, the hydrogen production rate is twice the oxygen permeation rate:…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results of Wang et al [24] and Lee at al. [13] both revealed that, based on the water splitting reaction and oxygen permeation process in a membrane reactor, the hydrogen production rate is twice the oxygen permeation rate:…”
Section: Governing Equationsmentioning
confidence: 99%
“…If the water splitting reaction is fast enough, then the oxygen permeation process will be the controlling step of the hydrogen production. The studies of Park et al [8] on the La 0.7 Sr 0.3 Cu 0.2 Fe 0.8 O 3-δ (LSCuF−7328) membrane reactor, Hong et al [9] and Habib et al [10] on the La 0.1 Sr 0.9 Co 0.9 Fe 0.1 O 3-δ (LSCoF−1991) membrane reactor, Ben-Mansour et al [11] on the Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O x (BSCoF−5582) membrane reactor, Jiang et al [12] on the BaCo x Fe y Zr 1-x-y O 3-δ (BCoFZ) membrane reactor, Lee et al [13] on La 0.6 Sr 0.4 Ti 0.2 Fe 0.8 O 3-δ (LSTF−6428) membrane reactor, and Zhu et al [1] on La 0.9 Ca 0.1 FeO 3-δ (LCF−91) membrane reactor all show that, compared with inert gas, the use of reducing/reacting gas as a sweep gas can improve the oxygen permeability of the membrane reactor, thus leading to a higher hydrogen yield.…”
Section: Introductionmentioning
confidence: 99%